Co-occurrence of Kimura’s Disease and Keratoconus: A Case Report (International Journal of Scientific Research and Management (IJSRM), 2024)
Kimura disease, often referred to as eosinophilic granuloma, is an uncommon and long-lasting condition that is mostly seen in people of Asian ancestry. Early signs include increased levels of IgE in the blood, nodules under the skin, and swelling of the lymph nodes. Keratoconus is a disorder where both corneas get steeper and vision is reduced. It is not genetically connected to Kimura disease, although both illnesses are more common among Asian people. Performing a histopathological investigation of the mass is essential in order to get an accurate diagnosis. This case reports a 24-year-old male patient living in Saudi Arabia who had a growth on his face that extended above and below the medial canthus of his eye. The patient also had a gradual decrease in vision in both eyes. The patient received a comprehensive biopsy procedure and topographical examinations. The biopsy findings indicated the presence of angiolymphoid hyperplasia with eosinophilia, and no accompanying lymphadenopathy was seen. The diagnosis of Keratoconus was verified by the examination of the topography. Considering these results, the main therapeutic option is surgical removal of the tumor. This case report offers valuable insights into the diagnostic criteria, differential diagnosis, and management of Kimura disease, specifically in relation to keratoconus. Additionally, it contributes to the existing literature by presenting the first documented case of Kimura disease with concurrent keratoconus.